Non-Fluent Speech in Frontotemporal Lobar Degeneration - Ash, Sharon (2009)
We investigated the cognitive and neural bases of impaired speech fluency, a central feature of primary progressive aphasia. Speech fluency was assessed in 35 patients with frontotemporal lobar degeneration (FTLD) who presented with progressive non-fluent aphasia (PNFA, n=11), semantic dementia (SemD, n=12), or a social and executive disorder without aphasia (SOC/EXEC, n=12). Fluency was quantified as the number of words per minute in an extended, semi-structured speech sample. This was related to language characteristics of the speech sample and to neuropsychological measures. PNFA patients were significantly less fluent than controls and other FTLD patients. Fluency correlated with grammatical expression but not with speech errors or executive difficulty. SemD and SOC/EXEC patients were also less fluent than controls. In SemD, fluency was associated with semantically limited content. In SOC/EXEC, fluency was associated with executive limitations. Voxel-based morphometry analyses of high-resolution MRI related fluency to gray matter volume in left inferior frontal, insula, and superior temporal regions for the entire cohort of FTLD patients. This region overlapped partially distinct atrophic areas in each FTLD subgroup. It thus appears to play a crucial role in speech fluency, which can be interrupted in different ways in different FTLD subgroups.